CLINICIANS APPROACH TO EUTHANASIA IN THE PROVINCE OF KHYBER PAKHTUNKHWA - Khan, Mir Azam; Javaid, Arshad; Sajjad, Hassan; Ahmad, Fahad; Khattak, Afaq; Khan, Noman; Adnan, Muhammad Atta-ur-Rahman (Journal of Postgraduate Medical Institute, 2015)
Objective: To determine the knowledge of clinicians and their opinion about legalization, obstacles in practicing euthanasia and factors that may compel them to practice euthanasia. Methodology: A questionnaire based descriptive study was conducted at public and private hospitals of Khyber Pakhtunkhwa. A questionnaire was dis-tributed randomly to 540 doctors of different specialties and general practi -tioners. Questions were related to their knowledge, views about legalization, factors and obstacles in practicing euthanasia. The questionnaire was collect -ed from the doctors who filled the form and consented to participate in the study. Results: The response rate was 55%, among them 79% were males. Only 61% (185) knew the meaning of euthanasia, whereas 36% (109) knew about its guidelines and 2% (6) had no knowledge of euthanasia. Amongst clinicians who knew about euthanasia, 84% did not and 16% agreed with its legalization. Reasons mentioned for disagreement with its legalization were religion 95%, moral 61%, ethical 44%, emotional 41% and social 37%. Of those clinicians who agreed with its legalization, 90% would and 10% would not practice it on their patients. Out of them 40% would adopt no re-suscitation method, 40% would administer lethal drugs and 20% would with -hold or withdraw the treatment. Conclusion: Majority of responding clinicians were not aware of euthanasia and any related guidelines. They disagreed with the practice as well as legal-ization of euthanasia.